DAMPAK REVALUASI ASET TETAP TERHADAP PAJAK PENGHASILAN YANG TERHUTANG - Atikasari, Teti Tri; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTFixed assets is one of some company accounts which have large value. The current value of assets will not be the same with recorded on the financial position report. This factor encourage companies to conduct revaluation on their fixed assets to make it conform with the fair value. The revaluation of fixed assets is not the routin activity and involves professional to make it more effective in minimizing the burden of corporate tax. The Regulation No. 191/PMK.010/2015 i.e. Final tariff reduction income tax on the difference of fixed assets revaluation and the Regulation No. 169/PMK.010/2015 which determine the magnitude of the comparison between account receivable and capital expenditure for the calculation of Income Tax as many as four appeal one (4:1). The research method has been done by using descriptive method and qualitative approach. The amount of burden of payable corporate income tax when it does not run the assets revaluation is Rp. 987,169,750. When conducts assets revaluation is Rp 270,970,750. It has been found that with this condition the amount of the burden of the payable corporate income tax is smaller when the company conducts fixed assets revaluation than the company does not conduct fixed assets revaluation.Keywords:Fixed assets revaluation, Minister of Finance Regulation No.191/PMK.010/2015, Minister of Finance Regulation No.169/PMK.010/2015